2018
DOI: 10.1007/s13337-018-0481-1
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 DNA detection and variant analysis in patients with multiple sclerosis

Abstract: Several studies reported a complex interplay between viral infections and neural cells leading to multiple sclerosis. A role for some viral infections has been proposed in MS. In this study, DNA sequences of human herpesvirus 8 (HHV-8) were searched in the peripheral blood of 54 patients with multiple sclerosis and 130 healthy subjects using nested-PCR assay to amplify ORF26 locus. Furthermore, HHV-8 positive samples were subjected to a nested-PCR to amplify K1 gene of HHV-8 followed by direct nucleotide seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…As we mentioned before numerous studies have reported an interaction between viral infection and neural cells leading to multiple sclerosis. Marashi et al (2018) examined peripheral blood looking for DNA sequences of HHV-8 in 54 multiple sclerosis patients and 130 healthy subjects, detecting the virus in 18.5% of the patients and 3% of controls. HHV-8 infection has also been reported in patients with acquired immune deficiency syndrome (AIDS) associated with Kaposi sarcoma (Corbellino et al, 1996;Ogoina et al, 2011).…”
Section: Klks Associated To Viral Infections That Can Affect the Cnsmentioning
confidence: 99%
“…As we mentioned before numerous studies have reported an interaction between viral infection and neural cells leading to multiple sclerosis. Marashi et al (2018) examined peripheral blood looking for DNA sequences of HHV-8 in 54 multiple sclerosis patients and 130 healthy subjects, detecting the virus in 18.5% of the patients and 3% of controls. HHV-8 infection has also been reported in patients with acquired immune deficiency syndrome (AIDS) associated with Kaposi sarcoma (Corbellino et al, 1996;Ogoina et al, 2011).…”
Section: Klks Associated To Viral Infections That Can Affect the Cnsmentioning
confidence: 99%
“…The Kaposi sarcoma-associated herpes virus infection pathways were enriched in the gene set uploaded. A study showed that the human herpes virus 8 genomes were detected in 10 out of 54 individuals with MS and 4 out of 130 control samples when nested PCR was performed (Marashi et al, 2018). Forkhead box O1 in short FoxO signaling pathway was also enriched in the geneset.…”
Section: Common Enriched Kegg Pathwaysmentioning
confidence: 99%
“…Oligoclonal bands (OCBs) directed against HHV-6 and EBV have been identified in MS patients [ 149 ], and OCBs against HSV-1 in the CSF of MS patients has also been reported [ 150 ], although this was not corroborated in all studies [ 151 ]. HSV-1 has been linked to demyelination in animal models [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ] and in humans [ 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ], and several studies have suggested other herpesviruses including HHV-6 [ 146 , 164 , 169 , 170 , 171 , 172 , 173 , 174 ], EBV [ 144 , 175 , 176 , 177 , 178 , 179 , 180 , 181 ] and HHV-8 [ 168 , 170 , 182 ] are risk factors for MS. In general, herpesvirus infections are more frequent in MS patients than in patients with other neurological diseases [ 138 ].…”
Section: Human Endogenous Retroviruses (Hervs)mentioning
confidence: 99%